A simulation package for heat insulation and condensation in multilayer building elements - Esin, T; Esin, EM (Begell House, Inc, 1999)
Solution of heat insulation and condensation problems in building shells are important issues to provide healthy buildings and human health. Many methods can be used for optimal design of multilayer building elements but they need complex calculations. In this work, analytical design method is used. A software named Building Shell Simulator is developed to simulate the behavior of heat and vapor in multilayer building shells and to show condensation zones if it occurs. As programming environment Borland C++ Builder for Win95 is used. It has fully visual and interactive user interface. The package helps architects for rapid and effective designing of multilayer building shells.
2nd Trabzon International Energy and Environment Symposium -- JUL 26-29, 1998 -- KARADENIZ TECH UNIV, TRABZON, TURKEY